Responses of a Coronal Hole to a Fast Flare-driven Coronal Wave - Zhang, Xiaofan; Chen, Huadong; Zhou, Guiping; Feng, Li; Su, Yang; Guo, Jinhan; Li, Leping; Lin, Wei; Ma, Suli; Shen, Yuandeng; Zheng, Ruisheng; Liu, Suo; et al. (Astrophysical journal. Letters, 2025)
Coronal waves, significant solar phenomena, act as diagnostic tools for scientists studying solar atmosphere properties. Here, we present a novel observation detailing how a coronal wave event, associated with an X5.0 class flare, influenced the properties of an adjacent coronal hole (CH) through interaction. The coronal wave was observed in both extreme-ultraviolet (EUV) observations from the Atmospheric Imaging Assembly on board the Solar Dynamics Observatory and Ly α observations from the Solar Disk Imager on board the Advanced Space-based Solar Observatory. Utilizing the method of differential emission measure, we found that as the coronal wave passed through, the adjacent CH experienced an increase in temperature from 1.31 to 1.43 MK and a rise in density from ∼1.62 × 10 8 to 1.76 × 10 8 cm −3 within the rising period of ∼7 minutes. Subsequently, after the wave passed, the entire CH transitioned to a new state with a slight temperature increase and a 14% decrease in density, with more pronounced changes observed at the CH’s boundary. Taking into account the impacts of radiative loss and heat conduction, the coronal wave was estimated to provide an average energy of 2.2 × 10 8 erg cm −2 to the CH during the short rising period. This study highlights the identification of the coronal wave in both EUV and Ly α observations, shedding light on the significant energy input, particularly within the CH. These findings provide new insights into better understanding kinematics of fast coronal waves, energy transfer processes open versus closed magnetic topologies, and the possible acceleration of solar winds.